The Effect of Audio Visual Educational Media in Increasing Knowledge Retention and Compliance with the Use of Personal Protective Equipment as an Effort to Prevent Occupational Health Risks among Apple Farmers - Payal Choundhury; Santiago Jorge Pereira (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aimed to determine the effect of audio-visual health education media on knowledge retention and compliance with personal protective equipment (PPE) use as a strategy to prevent occupational health risks among apple farmers in Kuala Pilah, Malaysia. Methodology: A pre-experimental one-group pretest–posttest design was conducted involving 20 apple farmers selected through total sampling. Data were collected at four time points: baseline (T0), immediately after intervention (T1), one week (T2), and two weeks (T3) post-intervention. Knowledge was measured using a structured questionnaire, while PPE compliance was assessed through observation and self-report. Repeated measures analysis and paired categorical tests were applied with a significance level of p < 0.05. Main Findings: The mean knowledge score increased from 56.4 at baseline to 82.7 immediately after the intervention, and remained significantly higher at 78.9 (week 1) and 74.6 (week 2) (p < 0.001). PPE compliance improved from 30.0% at baseline to 70.0% post-intervention and was maintained at 70–75% during follow-up (p < 0.05). Novelty/Originality of this study: This study provides integrated evidence on both sustained knowledge retention and measurable behavioral compliance using repeated follow-up assessments in an agricultural occupational health context, demonstrating the effectiveness of audio-visual media beyond immediate learning outcomes.